Validity of IntegratedE-Modules Contextual Teaching and Learning Approaches SubjectMatterElasticity to ImproveCritical Thinking Abilityof Students Senior High School - Utami, Nesia Nindri (Department of Physics Universitas Negeri Padang, 2024)
Students need to develop their critical thinking skills, which include the 4Cs of the 21st century: creativity, collaboration, communication, and critical thinking. These 4Cs are qualities that are essential for success in the modern world. So it's important to acquire knowledge that can sharpen critical thinking abilities. In three high schools in Sungai Punuh City, the pupils' critical thinking abilities were not as good as anticipated. The first research revealed that the lack of connections between the teaching materials and the usage of physics in daily life was the root of the students' poor critical thinking skills. 77% of students said that the professors' teaching resources did not incorporate real-world applications of physics. Textbooks predominate in the instructional resorces utilized, however they do not promote critical thinking or self-learning. Therefore, in order to develop students' critical thinking abilities, autonomous learning tools are required that meet their demands. In order to enhance critical thinking abilities, research was done on the construction of integrated e-modules using the CTL technique on material elasticity. The findings of expert validity tests are especially communicated in this study. Three experts from the Faculty of mathematics and natural sciences UNP Physics Department conducted the validity test, which had an average validity score of 85.7% in the extremely valid category. According to the validity test results, the e-module is combined with the CTL method to resources elasticity to improve critical thinking abilities that are prepared to be evaluated for applicability and efficacy in the actual world.